COMPETITIVENESS AND COMPETITIVE ORIENTATIONS: EVALUATION OF STUDENTS - G. Z. Efimova (Образование и наука)
Introduction. Education of a competitive student is a strategically significant problem of the system of higher education in modern social and economic conditions. Personal competitiveness and competitive orientations – priority quality of future expert for successful future professional experience.The aim of the present research is to study factors of competitive orientations formation and criteria for evaluation of competitiveness of student’s youth in the Russian society.Methodology and research methods. Results of theoretical researches of Russian and foreign researchers are generalized; secondary analysis of data based on results of sociological researches and analysis of official statistical data are carried out. The results of the sociological survey undertaken in 2017 on the basis of statistical methods were processed and studied by the instrumentality of IBM SPSS Statistics 23 program; 1196 students of institutions of higher and secondary vocational education of the Tyumen region took part.Results and scientific novelty. It is stated that senior students feel themselves more competitive. It is revealed that a quarter of students who took part in the survey, generally men, count themselves competitive. A continuous distance of goal-setting is recorded among these respondents; in every third case they have plans of professional growth for five and more years that allows them to build attractive competitive strategy.The level of the competitiveness is directly connected with such indicators as “social stratum”, “overall life satisfaction”, “self-esteem of health”, “tendency to lead a healthy lifestyle” and “the level of trust in the surrounding people”. Mostly the students oriented on competition look into the future with confidence and optimism.Respondents focused on the competitiveness were more tend to demonstrate their abilities and cause admiration, have a creative approach towards work, be ready for surprises, risk and adventures. At the same time, uncompetitive respondents try to be “simple and modest, not to attract attention to themselves”; focused on abidance by rules; avoid condemnation by the people surrounding them.Triple, and sometimes, fivefold gap between some indicators received on the basis of response for different block questions of the questionnaire among competitive and noncompetitive students, demonstrates formation of essentially various vital strategy.Practical significance. The emphasized factors of the formation of competitive orientations and criteria of competitiveness evaluation can provide a framework for the development of organizational and managerial decisions in the system of professional education.